Effect of theophylline on the rate of moderate to severe exacerbations among patients with chronic obstructive pulmonary disease - Cyr, Marie-Christyne (Blackwell Science Inc, 2008)
AIM: To determine the effectiveness of theophyllines in real clinical practice on moderate to severe exacerbations. METHODS: A cohort of 36 492 chronic obstructive pulmonary disease (COPD) patients aged ≥50 years was reconstructed from the health administrative databases of the province of Quebec, Canada, between 1 January 1995 and 31 December 2002 to compare users of theophyllines with users of inhaled corticosteroids (ICS) and users of long-acting β(2)-agonists (LABA) on their rate of moderate to severe COPD exacerbations. RESULTS: Users of theophyllines were found to be less likely than users of LABA [crude rates 84 vs. 91 per 100 patient-years, adjusted rate ratio (RR) 0.89, 95% confidence interval (CI) 0.84, 0.95] and users of theophyllines plus ICS were found to be less likely than users of LABA plus ICS (crude rates 114 vs. 112 per 100 patient-years, adjusted RR 0.89, 95% CI 0.87, 0.92) to have moderate to severe COPD exacerbations. Users of theophyllines were found to be more likely than users of ICS to have a COPD exacerbation (crude rates 84 vs. 77 per 100 patient-years, adjusted RR 1.07, 95% CI 1.04, 1.10), and this association was even stronger among patients who had at least three exacerbations in the year prior to cohort entry (crude rates 273 vs. 213 per 100 patient-years, adjusted RR 1.28, 95% CI 1.19, 1.38). CONCLUSION: The use of theophyllines was found to be associated with a reduction in the rate of COPD exacerbations among all COPD patients, but to be less effective than ICS among patients with frequent exacerbations.